PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PROBLEM BASED LEARNING (PBL) TERHADAP MOTIVASI BELAJAR SISWA KELAS XI SMA NWDI PANCOR - Indrawati; Wawan Muliawan; Sarwati; Humaidi (Cocos Bio, 2024)
This research aims to determine the validity and effectiveness of Project Based Learning Student Worksheets (LKPD) in increasing student learning motivation on the Human Digestive System material. This type of research is development research. This research uses the Bord and Gall development model. This model consists of 10 stages, but in its implementation it was simplified into 5 stages which were adapted to the needs and limitations of the research. The test subjects in this research were 1 material expert, 1 design expert, 1 biology teacher and 24 students. The data collection technique used in this research is a learning motivation questionnaire. The data collection instrument used in this research is an instrument to measure the validity of the LKPD in the form of a material expert validation sheet and a design expert validation sheet. The instrument for knowing teacher responses and student responses to LKPD is in the form of a questionnaire. Data analysis in this research uses instrument validity, student response results, and analysis of learning motivation questionnaire results. The results of the validity analysis of the material expert obtained 83.82% with valid criteria, the results of the validity analysis of the design expert obtained 88.33% with very valid criteria, and the results of the teacher response analysis obtained 98.68% with very good criteria as well as the results of the analysis of participant responses. students on LKPD obtained 90.07% with very good criteria. The results of the analysis of the student learning motivation questionnaire obtained a percentage of 91.14% with the criteria for achieving learning objectives (KKTP) being very effective. From the results of the research trial subjects, it shows that the Project Based Learning LKPD is suitable for use according to the needs of students.